The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fcimb.2020.545371
|View full text |Cite
|
Sign up to set email alerts
|

Various Adjuvants Effect on Immunogenicity of Puumala Virus Vaccine

Abstract: Various adjuvant effects on the immunogenicity of the candidate inactivated Puumala virus vaccine were detected in BALB/c mice. Adjuvants under study were: aluminum hydroxide, spherical particles of Tobacco mosaic virus coat protein, B subunit of heat-labile enterotoxin of Escherichia coli, and low endotoxic lipopolysaccharide of Shigella sonnei. Aluminum hydroxide (1 mg/ml) did not affect neutralizing antibodies' induction and vaccine stability during storage compared to immunization with the vaccine without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 50 publications
0
17
0
1
Order By: Relevance
“…We did not immunize mice with SPs alone because it was not relevant for this study. However, in our previously studies we have shown that after administration of SPs alone, antibodies to candidate vaccine antigen were absent in sera of immunized animals ( Kurashova et al, 2020 ). The immunization schedule and the groups’ description summary are represented in Figure 4 .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…We did not immunize mice with SPs alone because it was not relevant for this study. However, in our previously studies we have shown that after administration of SPs alone, antibodies to candidate vaccine antigen were absent in sera of immunized animals ( Kurashova et al, 2020 ). The immunization schedule and the groups’ description summary are represented in Figure 4 .…”
Section: Resultsmentioning
confidence: 95%
“…The problem of individual proteins’ low immunogenicity was solved by the application of a novel safe adjuvant, spherical particles (SPs), generated by thermally induced structural remodeling of the tobacco mosaic virus (TMV). Previously, we have published pioneering works on the characterization of SPs’ properties, including adjuvant activity and safety ( Atabekov et al, 2011 ; Nikitin et al, 2011 , 2013 , 2018b , 2018c ; Karpova et al, 2012 ; Trifonova et al, 2014 , 2015 ; Ksenofontov et al, 2019 ; Evtushenko et al, 2020 ) and several vaccine candidates against pathogens of a viral and bacterial nature have been developed ( Trifonova et al, 2017 ; Nikitin et al, 2018a ; Kurashova et al, 2020 ; Ryabchevskaya et al, 2020 , 2021 ). The authors assume that SPs in compositions with a target antigen act as a depot and this determines the adjuvant effect ( Trifonova et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The amino acid composition of the surface of SPs diff ers signifi cantly from that of TMV virions [31]. Avian infl uenza virus polyvalent epitopes of HA and M2 proteins [41] Rabies virus monovalent inactivated virion [42] Rotavirus monovalent epitope of VP6 protein [40] Puumala virus (hantavirus) monovalent inactivated virion [38] Coronavirus SARS-CoV-2 polyvalent RBD domain, conserved fragments of the S2 subunit [7] Bacillus anthracis bacterium monovalent protective antigen -PA [35] As a result of thermal rearrangement, TMV SPs acquire properties diff erent from those of virions. In particular, they have unique adsorption capabilities.…”
Section: Structurally Modified Plant Virusesmentioning
confidence: 99%
“…Adjuvants not only enhance immune response and its duration, but can also infl uence the type of response (humoral and/or cellular). Adjuvants stimulate immune response to diff erent antigens with diff erent effi cacy: for example, adjuvants based on aluminum compounds are ineff ective in some cases [36][37][38][39].…”
Section: Structurally Modified Plant Virusesmentioning
confidence: 99%
See 1 more Smart Citation